The relationship between the massive nesting of the olive ridley sea turtle (Lepidochelys olivacea) and the local physical environment at La Escobilla, Oaxaca, Mexico, during 2005 - Coria-Monter, Erik; Durán-Campos, Elizabeth (HIDROBIOLÓGICA, 2017)
Background. Sea turtles of the genus Lepidochelys exhibit a complex and synchronous mass-nesting behavior termed arribada. Goals. This paper analyzes the local physical environment during the arribada events that occurred in 2005 at La Escobilla, Oaxaca, Mexico. Methods. Daily night patrols were conducted from May to November 2005, along the nesting zone. Daily records for air temperature and rainfall were obtained from the automatic weather station by the Comisión Nacional del Agua. Sea surface temperature and salinity fields were obtained from the Hybrid Coordinate Ocean Model (HYCOM), and surface ocean currents were obtained from the Asia-Pacific Data Research Center. Results. The analyses showed five arribada events during the period. A common feature was the presence of eddies and strong currents at the beginning of each arribada. A correlation of statistical significance was observed between the abundance of the arribada and the current speed (R = 0.93, R2 = 0.86, p = 0.04). The correlation with salinity showed values of R = 0.55, R2 = 0.31, p = 0.32, whereas correlation with rainfall was R = 0.53, R2 = 0.28, p = 0.14. A weak correlation was observed with air temperature (R = 0.35, R2 = 0.12, p = 0.59) and with sea surface temperature (R = 0.23, R2 = 0.05, p = 0.66). Conclusions. Although sea turtles are strong swimmers, the proximity to favorable oceanic currents generated by eddies might be related to the beginning of the arribada, considering that this current might provide energy savings and accumulate chemical compounds and food in the water column.